(untitled) (Global Journal of Science Frontier Research, 2014)
Background/Aim: Hepatitis B surface antigen(HBsAg) is routinely detected qualitatively in Hepatitis B Virus(HBV) infection where its persistence beyond 6 months defines chronic hepatitis B(CHB) infection. Hepatitis B e antigen (HBeAg) usually indicates active HBV replication and risk of transmission of infection. In spite of the emerging use of chemiluminescence based quantitative HBsAg assays for therapeutic monitoring of the patients, we measured HBsAg concentration by sandwich ELISA as a cost effective alternative to ascertain the role of HBsAg levels as surrogate marker of untreated HBeAg negative subjects having CHB infection.